School Counselor Self-Advocacy: The Role of Local Cultural Values of Sipakatau, Sipakalebbi, and Sipakainge - Astinah; Nurul Fajriani; Nasriani; Dupriani (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
The role of guidance and counseling teachers is often marginalized within the institutional structure of schools. Therefore, developing self-advocacy grounded in local cultural values becomes a strategic means of enhancing the legitimacy and effectiveness of counseling services. This research aims to explore the self-advocacy practices of school counselors at SMPN X in Parepare City and to analyze the application of local cultural values—sipakatau, sipakalebbi, and sipakainge—in strengthening guidance and counseling services. The data collected using a qualitative approach with a case study method through in-depth interviews, participant observation, and document analysis. The research involved three guidance counselors with more than five years of experience, supported by principals, teachers, students, and parents. Data analysis was conducted through the processes of transcription and coding of interview and observation data. The data were then analyzed thematically to identify meaningful patterns and relationships. The validity of the research findings was ensured through data triangulation, as well as the implementation of member checking and peer debriefing procedures. The findings show that self-advocacy enables BK teachers to expand their roles through communication and active collaboration with school stakeholders, which impacts the strengthening of counseling services. Self-advocacy grounded in sipakatau helps foster respectful interactions among students, teachers, principals, and parents; sipakalebbi enhances social relationships through appreciation and respect; and sipakainge ensures the effectiveness of preventive guidance through mutual reminders. These findings affirm the importance of integrating self-advocacy and local cultural values in creating inclusive and socially relevant counseling services. This study is expected to contribute to the development of culturally grounded counseling theory and practice adaptable across various school contexts.